Balkan family structure and the European pattern : demographic developments in Ottoman Bulgaria - Todorova, Marii͡a Nikolaeva (Pasts incorporated, 2006)
This study, which is an updated, extended, and revised version of the out-of-print 1993 edition, reassesses the traditional stereotype of the place of the Balkans in the model of the European family in the nineteenth century on the basis of new source material and by synthesizing existing research. The work first analyzes family structure and demographic variables as they appear in population registers and other sources, and the impact of these findings on theoretical syntheses of the European family pattern. On most features, such as population structure, marriage and nuptiality, birth and fertility, death and mortality rates, family and household size and structure, as well as inheritance patterns, the Balkans show an enormous deal of internal variety. This variability is put in a comparative European context by matching the quantifiable results with comparable figures and patterns in other parts of Europe. The second section of the book is a contribution to the long-standing debate over the zadruga, the complex, collective, joint or extended family in the Balkans. Finally, the book considers ideology and mythology and the ways it has adversely affected scholarship on the family, and broadly on population history.